Control of dendritic cell maturation and function by triiodothyronine - Mascanfroni, Ivan Darío (2008)
Accumulating evidence indicates a functional crosstalk between immune and endocrine mechanisms in the modulation of innate and adaptive immunity. However, the impact of thyroid hormones (THs) in the initiation of adaptive immune responses has not yet been examined. Here we investigated the presence of thyroid hormone receptors (TRs) and the impact of THs in the physiology of mouse dendritic cells (DCs), specialized antigen-presenting cells with the unique capacity to fully activate naive T cells and orchestrate adaptive immunity. Both immature and lipopolysaccharide-matured bone marrow-derived DCs expressed TRs at mRNA and protein levels, showing a preferential cytoplasmic localization. Remarkably, physiological levels of triiodothyronine (T3) stimulated the expression of DC maturation markers (major histocompatibility complex II, CD80, CD86, and CD40), markedly increased the secretion of interleukin-12, and stimulated the ability of DCs to induce naive T cell proliferation and IFN-gamma production in allogeneic T cell cultures. Analysis of the mechanisms involved in these effects revealed the ability of T3 to influence the cytoplasmic-nuclear shuttling of nuclear factor-kappaB on primed DCs. Our study provides the first evidence for the presence of TRs on bone marrow-derived DCs and the ability of THs to regulate DC maturation and function. These results have profound implications in immunopathology, including cancer and autoimmune manifestations of the thyroid gland at the crossroads of the immune and endocrine systems.